2020
DOI: 10.1136/bmjopen-2019-034354
|View full text |Cite
|
Sign up to set email alerts
|

What are potential barriers and enablers to patient and physician participation in Canadian cell therapy trials for stroke? A stakeholder interview study

Abstract: ObjectivesEarly phase cell therapy trials face many barriers to successful, timely completion. To optimise the conduct of a planned clinical trial of mesenchymal stem cell (MSC) therapy for chronic stroke, we sought patient and physician views on possible barriers and enablers that may influence their participation.DesignSemistructured interview study.SettingPatients were recruited from three rehabilitation centres in Ontario, Canada; physicians were recruited from across Canada through snowball sampling.Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…One common approach used to apply behavior change theory within health research is the Theoretical Domains Framework (TDF-see Box 1 for domains and definitions) [7 , 8] . Recent interview studies have utilized the TDF to explore barriers and enablers to enacting behaviors within clinical trials, such as intervention delivery and participant recruitment [9][10][11] . However, the TDF has not previously been used to identify barriers and enablers to retention in trials from the perspectives of trial participants [12] .…”
Section: Introductionmentioning
confidence: 99%
“…One common approach used to apply behavior change theory within health research is the Theoretical Domains Framework (TDF-see Box 1 for domains and definitions) [7 , 8] . Recent interview studies have utilized the TDF to explore barriers and enablers to enacting behaviors within clinical trials, such as intervention delivery and participant recruitment [9][10][11] . However, the TDF has not previously been used to identify barriers and enablers to retention in trials from the perspectives of trial participants [12] .…”
Section: Introductionmentioning
confidence: 99%
“…A recent qualitative study explored clinician reported challenges to recruitment in trials set within emergency care and identi ed a range of in uential factors, including: supporting the patients to engage with the research, issues around equipoise, surgeon preferences, interpretation of eligibility criteria, and balance of clinical vs. research roles (8). In addition, other recent studies have incorporated behavioural frameworks to identify challenges for trial recruitment and intervention delivery (3,4,10,11). However, the majority of these existing studies do not go as far as developing potential solutions and implementing them within the trial to proactively address the challenges identi ed.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the behavioural in uences of core trial processes (and optimising them where improvements are needed) could help contribute to understanding the overall success or failure of the trial. Behavioural approaches to understand and change trial process behaviours are starting to emerge in the literature, but to date have largely focussed on identifying behavioural problems for trial recruitment and retention (3)(4)(5)(6). The applicability of a behavioural science approach to both identify trial process barriers and implement strategies to address these challenges warrants further attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of time on the part of physicians, both for the identification of ongoing trials and the patients that would be suitable for inclusion, is another major hurdle to trial recruitment. [79][80][81] Reducing the administrative burden on physicians would allow them to more efficiently screen patients and perform clinical trial duties.…”
Section: Reducing the Administrative Burden Of Ibd Clinical Trialsmentioning
confidence: 99%